Long term effect of fertilizer, farm-yard manure and lime on yield sustainability and soil organic carbon pools under soybean (Glysine max)–wheat (Triticum aestivum) cropping system in Alfisol - KUMARI, GEETA; THAKUR, S. K.; KUMAR, VIPIN; KUMAR, NAVNIT; SINGH, S. K. (Journal of Soil and Water Conservation, 2020)
The experiment was conducted under Long–Term Fertilizer Experiment (LTFE) to evaluate the impact of farm-yard manure, fertilizer and lime application on yield trends and soil organic carbon pools and their inter–relationship with sustainable yield index (SYI) in soybean (Glysine max L.)–wheat (Triticum aestivum L.) cropping system at BAU, Ranchi. The treatments were control, 100%N, 100%NP, 100%NPK, 100% NPK+FYM, 100%NPK+ lime, and 150%NPK. The result indicated that continuous application of 100%NPK along with FYM recorded increasing yield of soybean (0.12 q/ha/yr) and wheat (0.42 q/ha/yr) while imbalanced use of fertilizers viz. 100%N, 100%NP showed decline in yield trend. The application of 100%NPK+ FYM recorded highest value of SYI for soybean (0.61) and wheat (0.42), respectively followed by 100%NPK along with lime. However, the value of SYI was least due to the application of N alone. Continuous organic manure application along with inorganic fertilizer significantly influenced the total organic carbon, CO2 evolution, soil microbial biomass carbon and nitrogen (SMBC and SMBN), water soluble carbon (WSC), water soluble carbohydrates (WSCh). The relationships between sustainable yield index (SYI) and soil quality parameters indicated that the total and active fractions of SOC ultimately support the productivity and in contrast their losses reduce the nutrient supplying capacity of soil. Thus, continuous application of 100%NPK along with lime, and FYM are beneficial for restoration of SOC, maintaining soil fertility and yield sustainability of soybean – wheat cropping system in Alfisol.